Heat retention analysis with thermal encapsulation of powertrain under natural soak environment. (February 2020) - Yuan, R.; Dutta, N.; Sivasankaran, S.; Jansen, W.; Ebrahimi, K.
Highlights: Demonstrate 3D CFD of buoyancy-driven convection flow resolved on a full-geometry passenger car. A transient CFD - heat transfer modelling predicted cool-down behaviours during the static soak. Additional heat retention benefits characterised with vehicle-mounted-encapsulation design. A cost-effective CAE tool developed for heat retention analysis and encapsulation design. The CAE will aid the design development to achieve reduced CO2 emissions and fuel consumption. Abstract: This paper investigates high fatality modelling of vehicle heat transfer process during natural soak environment and heat retention benefits with powertrain encapsulations. A coupled computer-aided-engineering (CAE) method utilising 3D computational-fluids-dynamics (CFD) and transient thermal modelling was applied to solve buoyancy-driven convection, thermal radiation and conduction heat transfer of vehicle structure and fluids within. Two vehicle models with different encapsulation layouts were studied. One has engine-mounted-encapsulation (EME) and the other has additional vehicle-mounted-encapsulation (VME). Coupled transient heat transfer simulations were carried out for the two vehicle models to simulate their cool-down behaviours of 9 h static soak. The key fluids temperatures' cool-down trajectories were obtained and correlated well with vehicle test data. Increased end temperatures were seen for both coolant and oils of the VME model. This provides potential benefits towards CO2 emissions reduction and fuel savings. The air paths and thermal leakages with both encapsulations were visualised. Reduced leakage pathways were found in the VME design in comparison with the EME design. This demonstrated the capability of embedded CAE encapsulation heat retention modelling for evaluating encapsulation designs to reduce fuel consumption and emissions in a timely and robust manner, aiding the development of low-carbon transport technologies.